The role of diet in chronic urticaria - Fiqnasyani, Siti Efrida; Widhiati, Suci; Kariosentono, Harijono; Irawanto, Muhammad Eko; Oktavriana, Triasari (Journal of Pakistan Association of Dermatologists, 2023)
Background Chronic urticaria symptoms are benign and self-limiting. However, chronic urticaria with systemic symptoms can be life-threatening and may be an early sign of anaphylactic shock. This systematic review was conducted to recognize and understand the clinical features of urticaria and the role of diet modification in chronic urticaria to minimise the side effect of long-term therapy. Â Methods A primary literature search using preferred reporting items for systematic reviews and meta-analyses (PRISMA) was conducted using PubMed and Science Direct databases in January 2021. Â Results A total of 10 articles were included in this study. Some diets and conditions were recommended to be avoided in patients with chronic urticaria are galactose-Î±-1,3-galactose allergy (Î±-gal), Anisakis simplex, pseudo allergens, gluten, food additives and histamine. Supplementation with diamine oxidase, vitamin D and probiotics was beneficial. Â Conclusion Diet modification in chronic urticaria patients receiving long-term medical therapy must be done to reduce drug side effects. Consumption of foods suspected of causing urticaria should be avoided for three consecutive weeks, especially for pseudoallergenic foods and histamine-containing foods. Moreover, patients should avoid consuming certain foods that can cause nutritional deficiencies, so further consultation with a nutritionist is needed. Â